Immune response in the adipose tissue of lean mice infected with the protozoan parasite Neospora caninum. Issue 2 (June 2015) - Teixeira, Luzia; Moreira, João; Melo, Joana; Bezerra, Filipa; Marques, Raquel M.; Ferreirinha, Pedro; Correia, Alexandra; Monteiro, Mariana P.; Ferreira, Paula G.; Vilanova, Manuel
Summary The adipose tissue can make important contributions to immune function. Nevertheless, only a limited number of reports have investigated in lean hosts the immune response elicited in this tissue upon infection. Previous studies suggested that the intracellular protozoan Neospora caninum might affect adipose tissue physiology. Therefore, we investigated in mice challenged with this protozoan if immune cell populations within adipose tissue of different anatomical locations could be differently affected. Early in infection, parasites were detected in the adipose tissue and by 7 days of infection increased numbers of macrophages, regulatory T (Treg) cells and T‐bet+ cells were observed in gonadal, mesenteric, omental and subcutaneous adipose tissue. Increased expression of interferon‐γ was also detected in gonadal adipose tissue of infected mice. Two months after infection, parasite DNA was no longer detected in these tissues, but T helper type 1 (Th1) cell numbers remained above control levels in the infected mice. Moreover, the Th1/Treg cell ratio was higher than that of controls in the mesenteric and subcutaneous adipose tissue. Interestingly, chronically infected mice presented a marked increase of serum leptin, a molecule that plays a role in energy balance regulation as well as in promoting Th1‐type immune responses. Altogether, we show that an apicomplexa parasitic infection influences immune cellular composition of adipose tissue throughout the body as well as adipokine production, still noticed at a chronic phase of infection when parasites were already cleared from that particular tissue. This strengthens the emerging view that infections can have long‐term consequences for the physiology of adipose tissue.